STRATEGI PEMERINTAH DAERAH DALAM PEMBANGUNAN MELALUI PROGRAM DESA MAJU INHIL JAYA DI DESA KOTABARU SEBERIDA KECAMATAN KERITANG TAHUN 2015 - Padli, Ronal; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study describes the program Desa Maju Jaya Kotabaru Seberida village belonging to the group of advanced village with a population of 10,856 inhabitants made up of several ethnic groups include Malays, Bugis, Banjar, Java, and toing hua. In line with this diversity becomes an important development focus the attention of either the Development of human government, public services and infrastructure.The method used adlh qualitative descriptive. This research was conducted in the village of Kotabaru Seberida District of Keritang, with the formulation of the problem What is the success rate of the program Desa Maju Inhil Jaya in Kotabaru village Siberida based on objective and form of development that is loaded in the Regional Regulation No. 5 of 2015 and What are the factors that become obstacles in Program implementation Inhil Maju Jaya village in Kotabaru village Siberida years 2014-2015.From the research it can be seen that the Strategy of Local Government in development through village programs developed Inhil glorious years in the village Kotabaru Seberida District of Keritang consist of a Strategy to Increase Public Participation, Increased Transparency Government, Improved Economy Village and inhibiting factor in the strategy of local governments in development through program developed village Inhil glorious years in the village Seberida Kotabaru District of Keritang including lack of attention to the Village Infrastructure, Political factors in the Region, social factors and Technology.Keywords: Local Government Development Strategy